Screening and kinetics of glutaminase and glutamate decarboxylase producing lactic acid bacteria from fermented thai foods - Sasimar Woraharn (2018)
© 2014, Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, SBCTA. All rights reserved. L-glutaminase and glutamic acid decarboxylase (GAD) catalyzes the hydrolysis of L-glutamine and glutamate, respectively. L-glutaminase widely used in cancer therapy along with a combination of other enzymes and most importantly these enzymes were used in food industries, as a major catalyst of bioconversion. The current investigation was aimed to screen and select L-glutaminase, and GAD producing lactic acid bacteria (LAB). A total of 338 LAB were isolated from fermented meat, fermented fish, fermented soya bean, fermented vegetables and fruits. Among 338 isolates, 22 and 237 LAB has been found to be positive for L-glutaminase and GAD, respectively. We found that 30 days of incubation at 35 ºC and pH 6.0 was the optimum condition for glutaminase activity by G507/1. G254/2 was found to be the best for GAD activity with the optimum condition of pH 6.5, temperature 40 ºC and ten days of incubation. These LAB strains, G507/1 and G254/2, were identified as close relative of Lactobacillus brevis ATCC 14869 and Lactobacillus fermentum NBRC 3956, respectively by 16S rRNA sequencing. Further, improvements in up-stream of the fermentation process with these LAB strains are currently under development.